2012
DOI: 10.1097/wnr.0b013e3283525af4
|View full text |Cite
|
Sign up to set email alerts
|

Reduced visual discrimination in cochlear implant users

Abstract: The aim of the study was to investigate low-level visual function in cochlear implant users. Spatial frequency discrimination was assessed in 16 adults with normal hearing and 18 adults with profound deafness who had a cochlear implant. Thresholds were measured with sinusoidal gratings using a two-alternative temporal forced-choice procedure combined with an adaptive staircase. Cochlear implant users had significantly poorer spatial frequency discrimination compared with normal hearing participants. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The long standing low auditory inputs in the developmental brain may contribute to decreased cortical thickness of extrastriate visual areas in M–P SNHL. Decreased cortical thickness in M–P SNHL may be associated with visual cognitive impairment in SNHL in a clinical setting (Dye and Hauser, 2014; Turgeon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The long standing low auditory inputs in the developmental brain may contribute to decreased cortical thickness of extrastriate visual areas in M–P SNHL. Decreased cortical thickness in M–P SNHL may be associated with visual cognitive impairment in SNHL in a clinical setting (Dye and Hauser, 2014; Turgeon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in screening and cochlear implantation (Monshizadeh et al, 2018), there are still many children with hearing loss that suffer from speech and language problems for a variety of reasons, including delayed diagnosis/intervention, failed follow‐up, sporadic attendance of auditory‐verbal therapy, and decision not to use hearing aids (Lü et al, 2011; Fitzpatrick et al, 2017). Additionally, even after intervention with hearing amplification and cochlear implants, SNHL places children at risk for language delay (Tomblin et al, 2015; Yoshinaga‐Itano et al, 2017), executive functioning deficits (Kronenberger et al, 2014), and visual cognitive impairment (Dye and Hauser, 2014; Turgeon et al, 2012), leading to life‐long consequences for affected children.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, imaging data suggests that vibrotactile stimuli can activate auditory regions in the deaf (Levänen et al, 1998; Schürmann et al, 2006; Sharma et al, 2007) and cortical over-representation of somatosensory evoked potentials in the left temporal region was found in deaf children using a CI (Charroó-Ruíz et al, 2013). Several data demonstrate that brain reorganization induced by deafness leads to behavioral changes for numerous perceptual tasks (Hanson, 1982; Neville and Lawson, 1987; Loke and Song, 1991; Bavelier et al, 2000, 2001, 2006; Bosworth and Dobkins, 2002; Heming and Brown, 2005; Turgeon et al, 2012), although it is unsure whether behaviorally advantageous (e.g., Bolognini et al, 2012). The effect of cross-modal reorganization raises important questions on the importance of hearing experience in shaping perceptual processing, but also in regards to cochlear implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Turgeon and colleagues [39] observed that CI compared to NH adults had higher visual discrimination thresholds for spatial frequency discrimination tasks; the stimuli used in their task were similar to those used here to manipulate visual attention. The authors of that study concluded that significant periods of progressive hearing loss experienced from birth or infancy (age at implantation ranged between 8 and 52) likely affected this 'low-level' visual ability, highlighting the complementary role that the auditory and visual systems might play in normal perceptual development.…”
Section: A N U S C R I P Tmentioning
confidence: 80%